Giving Ignatian Exercises at ecclesial frontiers - Heiding, S (2011)
The Spiritual Exercises of Ignatius of Loyola, the founder of the Jesuit order, presuppose Roman Catholicism, but are today made by many who are not Catholics. Moreover, even Roman Catholics who make Ignatian Exercises often are not spontaneously inclined to obey Roman ecclesiastical authority. Neither avoiding the ecclesial dimension nor an authoritarian ‘follow the rules!’ provides spiritual directors with adequate orientation when working with issues at Church frontiers. This dissertation in pastoral theology seeks to navigate a middle position by moving beyond the individualism and the a-historical assumptions of the existing relevant literature. The dissertation remains close to the Ignatian primary sources, in the awareness that the Ignatian tradition needs to be constantly updated and that the contemporary ecclesial frontiers are not fully foreseen in the canonical texts. The main hypothesis is that a notion is needed of a ‘pilgrim Church’ in space and time, with Christians who are related to one another in a deep and fundamental sense. The minor hypothesis is that the individual needs to be open towards and prepared to learn from the Roman Catholic Church, in order to understand and to be profoundly moved by these exercises, but not necessarily to become a Roman Catholic. Having presented and discussed various approaches in the writings of twentieth-century and recent thinkers, this thesis puts forward its own ecclesiological position informed by Charles Taylor, Hans-Georg Gadamer and Karl Rahner. The aim is to take Ignatian studies forward by combining relational anthropology, hermeneutics and a sacramental understanding of the Church, and to apply this synthesis to the practice of giving Ignatian Exercises. The final chapter discusses a selection of cases in the light of my ecclesiological position. The synthesis and application claim originality.